Prediktor immunological failure pada pasien HIV/AIDS di Yayasan Kerti Praja, Bali : studi kohort retrospektif - Prana Iswara, Ni Putu Ayu Astri; Sutarsa, I Nyoman; Sawitri, Anak Agung Sagung (E-Jurnal Medika Udayana; Vol 7 No 3 (2018): E-Jurnal Medika Udayana, 2018)
The occurrence of immunological failure (IF) in HIV/AIDS patients undergoing antiretroviral treatment at clinic Kerti Praja Foundation (YKP) Bali has never been evaluated. This study aimed to determine predictors of the occurrence IF in HIV/AIDS patients undergoing antiretroviral therapy. This study was an observational study with retrospective cohort design that used secondary data. Secondary data was obtained from medical records of 549 HIV/AIDS patients undergoing antiretroviral therapy in 2002-2012 period in YKP. The majority of patients in YKP are female sex workers, injecting drug users (IDUs), homosexual and bisexual. This study analyzes sociodemographic and clinical predictors influence on the IF. Analysis data using univariate, bivariate (chi-square) and multivariate was conducted. Only 205 patients of the total data that was eligible for analysis. A total of 61.0% of population are men with the dominant age 18-32 years (63.9%), and 13.7% experienced IF.. Multivariate analysis of the sexes, the supervisor taking medication, transmission lines infected with opportunistic infection, and CD4 counts baseline, showed only CD4 counts baseline variable is significant as a predictor of the occurrence IF. The results of this study indicate that baseline of CD4 counts plays an important role in the success of antiretroviral therapy in HIV / AIDS patients. Keywords: HIV/AIDS, ARV therapy, immunological failure, kerti praja foundation